FABRICATION OF COMPOSITE BALL SOCKET PIPELINE JACKET FOR SUBSEA FLOWLINES PROTECTION SYSTEMS - Nasrudin, Muhammad Arif (IRC, 2017)
Ball Socket Pipeline Jacket (BSPJ) is a protective system for onshore or offshore pipelines to shield cables from abrasion, corrosion, and impact while providing a system with custom additional submerged weight that suit the bottom stabilization of offshore flow-lines taking into account that BSPJ could be a sophisticated bending-restrictor system.